2001
DOI: 10.1177/10547730122159003
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Hypertensive Patients: An Observational Study of 21 Public Health Nurses

Abstract: Counselling in hypertension care relating to lifestyle changes, i.e. non-pharmacological treatment regarding smoking, alcohol, weight, diet, physical activity and stress, aims to reduce complications such as stroke and myocardial infarction. Many patients have several risk factors to deal with. There are few studies of nursing in hypertension care in Sweden and this issue therefore needs to be investigated in greater detail.The aims of this thesis were to analyse the communication between patients and nurses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Psychosocial counselling aims specifically to increase understanding and to motivate lifestyle change (Drevenhorn et al 2001). Two studies conducted interventions comprising education and psychosocial counselling, with limited reported effect on BP control.…”
Section: Education and Psychosocial Counsellingmentioning
confidence: 99%
“…Psychosocial counselling aims specifically to increase understanding and to motivate lifestyle change (Drevenhorn et al 2001). Two studies conducted interventions comprising education and psychosocial counselling, with limited reported effect on BP control.…”
Section: Education and Psychosocial Counsellingmentioning
confidence: 99%
“…RNs' communication could also be influenced by structural and sociocultural factors (Fakhr‐Movahedi et al, 2011). The communication could have a wide range of topics, for instance, related to information regarding illnesses or procedures (Efraimsson et al, 2015; O'Baugh et al, 2009; Pettersson et al, 2018; Roche & Jones, 2021), medical or therapeutic regimens (Carlsson & Pettersson, 2018; Drevenhorn et al, 2001; Duxbury et al, 2010; Hakimnia et al, 2014; Johnsson, Boman, et al, 2018; Kim et al, 2001; Manias & Williams, 2007; Mulder et al, 2014; Pettersson et al, 2018; Sandhu et al, 2009; Sayah et al, 2014) or non‐pharmacological topics, such as diet and physical activity (Drevenhorn et al, 2001; Mulder et al, 2014; Sayah et al, 2014) and health behaviours (Mulder et al, 2014). Psychosocial or socioemotional content was also common (Drevenhorn et al, 2001; Pettersson et al, 2018) involving small talk (de Leeuw et al, 2014; Sundler et al, 2020) and building relationships with the patients (Sandhu et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that the content of patients' communication with RNs included questions regarding medical issues, such as medications, medical examinations or symptoms (Drevenhorn et al, 2001; Kim et al, 2001), lifestyle issues (Wakefield et al, 2008), social talk (Kim et al, 2001), emotional cues (Eide, Sibbern, Egeland, et al, 2011; Finset et al, 2013; Heyn et al, 2011, 2013; Kettunen et al, 2000; Oguchi et al, 2011) or informational cues (Jansen et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Poskiparta et al (2001) analyzed nurses' words during health counseling sessions and found that the nurses empowered the patients by making use of the patients' knowledge. Drevenhorn et al (2001) found that most of the nurses' advice to hypertensive Swedish patients concerned the somatic aspects of health promotion. These studies all discussed the need for cultural sensitivity when motivating patients to change their lifestyle.…”
Section: Literature Reviewmentioning
confidence: 99%